Pengaruh Jangkauan Terhadap Keberlanjutan Keuangan BPJS Ketenagakerjaan - Pasaribu, Andri Ronaldo; Novianti, Tanti; Priyarsono, Dominicus Savio (School of Business, Bogor Agricultural University (SB-IPB), 2022)
BPJS Ketenagakerjaan has a function to provide social security for employees who work in Indonesia, both Indonesian citizens and foreign citizens, including Indonesian migrant workers. BPJS Ketenagakerjaan participation in Indonesia is mandatory by law, but based on internal data of BPJS Ketenagakerjaan (2021) there are still many workers who have not become participants. Therefore, outreach is needed by BPJS Ketenagakerjaan to implement its function. Where 99,9% of participants and prospective participants are workers who work in micro, small and medium scale enterprises (MSMEs). This study aims to analyze the effect of outreach on the financial sustainability of BPJS Ketenagakerjaan and to describe whether there is a trade-off or compatible. This study uses secondary data in the form of a cross-section consisting of 122 BPJS Ketenagakerjaan main branch offices in Indonesia in 2018. The analytical method used in this study is the Ordinary Least Square (OLS) method. The outreach carried out by BPJS Ketenagakerjaan has effect on its financial sustainability. It can be concluded that there is a trade-off between outreach and the financial sustainability of BPJS Ketenagakerjaan. This indicates that when BPJS Ketenagakerjaan wants to maintain its financial sustainability, it will reduce the outreach of services and potential participants. Keywords: outreach, financial sustainability, BPJS ketenagakerjaan, social security, Indonesia